660 PHYSIOTHERAPISTS PERCEPTIONS OF MECHANISMS FOR OBSERVED VARIATION IN PRACTICE DURING EARLY POSTOPERATIVE PHASE AFTER HIP FRACTURE. (8th March 2022) - Volkmer, B; Sadler, E; Lambe, K; Martin, F C; Ayis, S; Beaupre, L; Cameron, I D; Gregson, C L; Johansen, A; Kristensen, M T; Magaziner, J; Sackley, C; et al.
Abstract: Objective: To explore physiotherapists' perceptions of mechanisms to explain observed variation in early postoperative practice after hip fracture surgery demonstrated in a national audit. Methods: A qualitative semi-structured interview study of 21 physiotherapists working on orthopaedic wards at 7 hospitals with different durations of physiotherapy during a recent audit. Thematic analysis of interviews drawing on Normalisation Process Theory to aid interpretation of findings. Results: Four themes were identified: achieving protocolised and personalised care; patient and carer engagement; multidisciplinary team engagement across the care continuum; and strategies for service improvement. Most expressed variation from protocol was legitimate when driven by what is deemed clinically appropriate for a given patient. This tailored approach was deemed essential to optimise patient and carer engagement. Participants reported inconsistent degrees of engagement from the multidisciplinary team attributing this to competing workload priorities, interpreting 'postoperative physiotherapy' as a single professional activity rather than a care delivery approach, plus lack of integration between hospital and community care. All participants recognised changes needed at both structural and process levels to improve their services. Conclusion: Physiotherapists highlighted an inherent conflict between their intention to deliver protocolised care while allowing for an individual patient-tailored approach. This conflict has implications for how audit results should be interpreted, how future clinical guidelines are written, and how physiotherapists are trained. Physiotherapists also described additional factors explaining variation in practice which may be addressed through increased engagement of the multidisciplinary team and resources for additional staffing and advanced clinical roles.